Ionic medium effects on equilibrium constants .1. Proton, copper(II), cadmium(II), lead(II) and acetate activity coefficients in aqueous solution - Pezza, Leonardo [UNESP]; Molina, M.; deMoraes, M.; Melios, C. B.; Tognolli, J. O. (Elsevier B.V., 1996)
The molar single ion activity coefficients associated with hydrogen, copper(II), cadmium(II) and lead(II) ions were determined at 25 degrees C and ionic strengths between 0.100 and 3.00 M (NaClO4), whereas for acetate the ionic strengths were fixed between 0.300 and 2.00 M, held with the same inert electrolyte. The investigation was carried out potentiometrically by using proton-sensitive glass, copper, cadmium and lead ion-selective electrodes and a second-class Hg\Hg-2(CH3COO)(2) electrode. It was found that the activity coefficients of these ions (y(i)) can be assessed through the following empirical equations:log y(H) = -0.542I(0.5) + 0.451I; log y(Cu) = -1.249I(0.5) + 0.912I; log y(Cd) = -0.829I(0.5) + 0.448I(1.5);log y(Pb) = -0.404I(0.5) + 0.117I(2); and log y(Ac) = 0.0370I .
Keywords: ionic activity coefficients; ionic medium effects